Development of wireless structural health monitoring system for oil and gas pipelines - Shirazi, Ahmad A H S (2019)
Damage detection and life prediction of structures are important technological issues in both the academic and industrial fields. Numerous techniques have been proposed and developed for the detection of early damage in structural members. Research shows that periodical or visual inspections will not help resolve these issues, rather, having a continuous monitoring system is required for a particular system such as NPP (Nuclear Power Plant). Currently, Non Destructive Inspection (NDI) is used to inspect the area, however this can only be done in offline mode. Structural Health Monitoring (SHM) offers various methods to resolve issues such as these, nonetheless smart detecting methods are required before major failures occur, in order to avoid catastrophic failures in future. SHM can monitor this situation in active and passive states, either by online or offline monitoring. The use of SHM is to augment the NDI application and not to replace it. Then, the costs of a wired detecting system is high per channel, and requires focus on a wireless detecting method to reduce costs and avoid direct contact with hazardous areas. The main objective of this research is to develop of a wireless system or device embedded with a smart PZT sensor to detect flaws and structural defects on a selected investigated structure. Smart PZT sensors were used as an actuator and sensor, coupled with two XBees and one signal generator IC chip. The programme execution on the transmission and receipt of the ultrasonic guided wave via the PZT sensor was written in MATLAB. Basically, the developed source code is to receive serial data from one Xbee to another remote Xbee which is attached to the investigated structural system. The refined waveform response is utilised in an undergoing prognosis of the true structural status. The 4mm simulated hole on the pipe structure is benchmarked against its pristine condition in validating the effectiveness of the developed SHM wireless module. A marker plot software and Arduino micro controllers was used in wireless module for a further analysis and interpretation of results. The acquired results showed that no change for the pattern of wave in non-defected areas and despite being disrupted in the affected areas. The guided waves from wireless SHM system are able to propagate long distances and reach difficult access regions, hence the ultrasonic waveform device are continuously increasing for non-destructive evaluation and structural health monitoring in various structural applications.